2022
DOI: 10.3389/fcimb.2022.1045636
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin as a diagnostic marker for sepsis: A meta-analysis

Abstract: IntroductionSepsis is a life-threatening condition, and biomarkers are needed to diagnose sepsis fast and accurately. We aimed to perform this meta-analysis to investigate the diagnostic value of calprotectin on sepsis in critically ill patients.MethodsThe investigators searched MEDLINE, Embase, Web of Science and Cochrane Library. Studies were included if they assessed the diagnostic accuracy of serum calprotectin for sepsis in intensive care unit (ICU). We estimated its diagnostic value and explored the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Results of this study demonstrated an overall sensitivity of 0.88 (95% CI: 0.77–0.94) and a pooled specificity of 0.78 (95% CI: 0.65–0.87) with an overall AUC value of 0.90 (0.87, 0.92). Compared to other biomarkers, the pooled sensitivity in this meta-analysis was higher than the pooled sensitivity (0.79) in Chen et al’s meta-analysis investigating neutrophil to lymphocyte ratio (NLR) in the diagnosis of sepsis, while the specificity was lower than that (0.91) in Chen et al’s meta-analysis [ 30 ]; the comparison between PSP and calprotectin (sensitivity: 0.88 vs. 0.77, specificity: 0.78 vs.0.85) was similar to NLR [ 31 ]; Poggi’s meta-analysis assessing the accuracy of presepsin for the sepsis diagnosis showed that the pooled sensitivity and specificity were 0.93 (95% CI, 0.86–0.95) and 0.91 (95% CI, 0.85–0.95), respectively, which were higher than PSP [ 32 ]; the overall sensitivity and specificity were higher than those of CRP and PCT [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study demonstrated an overall sensitivity of 0.88 (95% CI: 0.77–0.94) and a pooled specificity of 0.78 (95% CI: 0.65–0.87) with an overall AUC value of 0.90 (0.87, 0.92). Compared to other biomarkers, the pooled sensitivity in this meta-analysis was higher than the pooled sensitivity (0.79) in Chen et al’s meta-analysis investigating neutrophil to lymphocyte ratio (NLR) in the diagnosis of sepsis, while the specificity was lower than that (0.91) in Chen et al’s meta-analysis [ 30 ]; the comparison between PSP and calprotectin (sensitivity: 0.88 vs. 0.77, specificity: 0.78 vs.0.85) was similar to NLR [ 31 ]; Poggi’s meta-analysis assessing the accuracy of presepsin for the sepsis diagnosis showed that the pooled sensitivity and specificity were 0.93 (95% CI, 0.86–0.95) and 0.91 (95% CI, 0.85–0.95), respectively, which were higher than PSP [ 32 ]; the overall sensitivity and specificity were higher than those of CRP and PCT [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increases after LPS administration found in our study indicate that CALP increases in sepsis, which is in line with the findings in humans where increases in this protein in serum have been found in patients with sepsis. This allows early diagnosis of sepsis on intensive care unit (ICU) admissions in adults [ 4 ] as well as infants [ 14 ], and is considered to be a tool that can aid timely sepsis management reducing mortality rates and avoiding unnecessary antibiotic treatment, thus improving antibiotic stewardship. The increases found in sepsis in pigs were higher than in the non-sepsis inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, CALP traditionally has been measured in faeces for the detection of inflammatory bowel disease and in serum as a biomarker of inflammation and sepsis [ 4 ]. However, it can also be quantified in saliva, where CALP has been reported to be increased in patients with active inflammatory bowel disease, suggesting that intestinal inflammation leads to increases in CALP in this sample type [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Procalcitonin and presepsin (PRSN) are both well-established biomarkers of sepsis and systemic infection (57). Procalcitonin, a prohormone of calcitonin, has been widely used as a diagnostic and prognostic biomarker in sepsis because of its rapid increase in response to bacterial infections and its correlation with the severity of the condition (58). Presepsin, also known as soluble CD14 subtype (sCD14-ST), is a more recently discovered biomarker that has shown promising results in the early detection of sepsis and the assessment of disease severity (59).…”
Section: Discussionmentioning
confidence: 99%